PENGARUH MOTIVASI TERHADAP KEAKTIFANANGGOTA KELOMPOK TERNAK SAPI PERAH DI DESA HARGOBINANGUN KECAMATAN PAKEM KABUPATEN SLEMAN - Irmanwidjasmara, Dzikri; Santosa, Agus; Dewantoro, Vandrias (Jurnal Dinamika Sosial Ekonomi, 2018)
The purposes of this research are: 1) To analyze level the activeness of the dairy cattle farmer in the Hargobinangun village 2) To analyze the influence of motivation on the activity of the group of dairy farmers member in the village of hargobinangun pakem district. The basic method of the research implementation is descriptive. The method of implementation of the research is survey. The location determination method is purposive. Sampling method is proportional random sampling. The analytical method uses multiple linear regression. The results shows that the level of activity of members farmer the cattle of dairy cows in the village of hargobinangun pakem district included in the category of active and Motivaring factor consists of Needs physiology, safety needs, the needs of belongingness and affection, influence the Activeness of members former the group cattle of dairy cows in the village of hargobinangun pakem district of sleman Regency.Keywords: Motivation, The Activeness Of Dairy Farmers Member.